Retirement financing dilemmas: experience of Singapore - Asher, Mukul G. (2004)
Singapore is now an affluent and rapidly aging society. It is also searching for ways to regain competitiveness in the face of globalisation and increasing competition from other countries. Even as the need for adequate social security provision is growing, Singapore's strong revealed preference for use of the central provident fund for socio-economic engineering and for political control are creating many dilemmas centering around governance, design of schemes, investment policies and whether to shift to a more appropriate multi-tier system. - Reproduced.
Keywords: Retirement - Singapore; Retirement